KERJASAMA KADIN INDONESIA DENGAN JAPAN EXTERNAL TRADE ORGANIZATION (JETRO) DALAM MENGEMBANGKAN UMKM INDONESIA (2022 - 2023) - Santoso, Sagit Hartono; Handoyo, Putri Ayu Wulandari (Moestopo Journal of International Relations (MJIR), 2023)
The purpose of this research is to find out how the Indonesian Chamber of Commerce and Industry collaborates with the Japan External Trade Organization (JETRO) in developing Indonesian MSMEs (2022- 2023). The method used in this research is a qualitative method with a descriptive type, and the data collection technique used is a literature study from various literature references, such as books, the internet, journals, print media and documents. The theories used in this research include the Theory of International Cooperation and Economic Diplomacy, because this research discusses the collaboration between the Indonesian Chamber of Commerce and Industry and JETRO, which is a collaboration between 2 countries, Indonesia and Japan. The results of this research explain how the collaboration between the Indonesian Chamber of Commerce and Industry and JETRO is developing Indonesian Micro, Small and Medium Enterprises (MSMEs), where this collaboration was realized by the formation of a program by Kadin and JETRO called wikieksport.jp. This program provides facilities to MSMEs in the form of information platforms, training, and business matching between Indonesian MSMEs and Japanese entrepreneurs. This program is carried out with the aim of encouraging Indonesian MSMEs to develop further and increase exports.